2017
DOI: 10.1016/j.chom.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Microbiome and Metabolome Cartography of a Diseased Human Lung

Abstract: Summary Our understanding of the spatial variation in the chemical and microbial make-up of an entire human organ remains limited, in part due to the size and heterogeneity of human organs and the complexity of the associated metabolome and microbiome. To address this challenge we developed a workflow to enable the cartography of metabolomic and microbiome data onto a three dimensional (3D) organ reconstruction built off radiological images. This enabled the direct visualization of the microbial and chemical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 39 publications
4
103
2
Order By: Relevance
“…This allowed a better visualization for correlation between microbial and molecular penetration. These visuals also revealed that local environments within the lung vary in terms of pathogen abundance, which can affect the metabolome in unique ways (126).…”
Section: The Respiratory Microbiome and Metabolismmentioning
confidence: 96%
“…This allowed a better visualization for correlation between microbial and molecular penetration. These visuals also revealed that local environments within the lung vary in terms of pathogen abundance, which can affect the metabolome in unique ways (126).…”
Section: The Respiratory Microbiome and Metabolismmentioning
confidence: 96%
“…Metabolomics is a promising technology that allows for simultaneous identification and relative quantitation of the major biochemicals present in cells, tissue, and/or body fluids. Information provided by metabolomics analysis regarding global metabolic alterations resulting from genetic and/or environmental exposures (eg, medications) may be used to monitor disease or treatment responses and has shown benefit in CF research . However, metabolomics, which can aid with patient stratification, and early intervention, has not been fully applied to CFTR modulator therapeutic monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Information provided by metabolomics analysis regarding global metabolic alterations resulting from genetic and/or environmental exposures (eg, medications) may be used to monitor disease or treatment responses and has shown benefit in CF research. [6][7][8][9][10][11][12][13][14][15][16][17] However, metabolomics, which can aid with patient stratification, and early intervention, has not been fully applied to CFTR modulator therapeutic monitoring. Recently, proteomics analysis (a method akin to metabolomics that focuses on protein analysis) of CF monocytes revealed monocyte function changes in response to Ivacaftor treatment, 18 suggesting the benefit of metabolite profiling after CFTR modulator initiation to determine biochemical changes.…”
mentioning
confidence: 99%
“…It is now appreciated that increased microbial immigration to the airways and decreased mechanisms of airway clearance facilitate selective microbial growth. As there are regional differences in the rates of microbial immigration, airway clearance and environmental selective pressures, in the lower airways, the composition of the microbiota also varies regionally …”
Section: Respiratory Microbiome Researchmentioning
confidence: 99%